2022
DOI: 10.1002/biot.202100401
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic pressure promotes chondrogenic differentiation and microvesicle release from human embryonic and bone marrow stem cells

Abstract: Mechanical stimulation plays in an important role in regulating stem cell differentiation and their release of extracellular vesicles (EVs). In this study, effects of low magnitude hydrostatic pressure (HP) on the chondrogenic differentiation and microvesicle release from human embryonic stem cells (hESCs) and human bone marrow stem cells (hBMSCs) are examined. hESCs were differentiated into chondroprogenitors and then embedded in fibrin gels and subjected to HP (270 kPa, 1 Hz, 5 days per week). hBMSC pellets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…Studies conducted in the past have indicated that HP at low loads (1–50 kPa) has an osteogenic impact on MSCs, whereas HP at physiological loads efficiently promoted chondrogenic differentiation[ 63 ]. This concept was also supported by several recent research works[ 60 , 64 ]. Some investigations, however, discovered a facilitative effect of physiological loading on MSCs' osteogenic differentiation[ 59 , 65 ], and a chondrogenic effect of low loading on MSCs[ 61 , 62 ].…”
Section: Physical Stimulisupporting
confidence: 59%
“…Studies conducted in the past have indicated that HP at low loads (1–50 kPa) has an osteogenic impact on MSCs, whereas HP at physiological loads efficiently promoted chondrogenic differentiation[ 63 ]. This concept was also supported by several recent research works[ 60 , 64 ]. Some investigations, however, discovered a facilitative effect of physiological loading on MSCs' osteogenic differentiation[ 59 , 65 ], and a chondrogenic effect of low loading on MSCs[ 61 , 62 ].…”
Section: Physical Stimulisupporting
confidence: 59%
“…Due to their unique biological roles, EVs coordinate complex processes, such as development, inflammation, tumorigenesis and even maintenance of a stem cell niche [ 201 ]. EVs release responses to external influences, such as cyclic hydrostatic pressure [ 202 ], oxidative stress [ 203 ] and hypoxia [ 204 ]. Types of EVs are distinguished for subclasses by their fundamental mechanisms of biogenesis, diversity of their composition and size [ 205 ] and selective cargo loading [ 206 , 207 ].…”
Section: Extracellular Vesicles (Evs) As a Tool For Cell Fate Manipul...mentioning
confidence: 99%
“…The presence of tetraspanin markers on the surface of EVs was assessed using the ExoView™ Tetraspanin Kit (NanoView Biosciences, United States) according to the manufacturers’ protocol and as previously described ( Gupta et al, 2020 ; Luo et al, 2021 ). Briefly, 35 µL of EV suspension (1:1,000 dilution in Incubation Solution) was incubated on the ExoView™ chip for 16 h. The chip was washed with Incubation Solution for 3 min, three times using Wash Solution and then with deionized water.…”
Section: Methodsmentioning
confidence: 99%